Community Organizing, Empowerment and Mobilization, and Information Education : The Revitalized KASIMBAYANAN Program of the Philippine National Police in Naga City - Rezaldy Jose R. Sambo (Jurnal Genesis Indonesia, 2025)
This study examined the implementation and outcomes of the Revitalized Kapulisan, Simbahan, at Pamayanan (KASIMBAYANAN) program of the Philippine National Police in Naga City. Specifically, it assessed the level of program implementation, identified strategies and practices employed, determined the effectiveness of police–church–community collaboration in crime prevention and crime solution, examined challenges and barriers encountered, tested the level of agreement between implementation and collaborative effectiveness, and proposed policy and practice improvements. The study adopted a descriptive–correlational research design utilizing both quantitative and qualitative approaches. Data were collected from 488 respondents composed of Philippine National Police personnel, barangay officials, and representatives of the religious sector through structured questionnaires, documentary analysis, and unstructured interviews. Quantitative data were analyzed using frequency count and percentage, weighted mean, ranking, and Kendall’s Coefficient of Concordance. Findings revealed that the Revitalized KASIMBAYANAN program was very much implemented in terms of community organizing, community empowerment and mobilization, and community information and education. Strategies and practices effectively strengthened partnerships among the police, church, and community, while collaborative efforts in crime prevention and crime solution were rated as very effective. However, challenges related to time constraints, financial sustainability, and mobility were identified. Results further indicated no significant agreement between the level of program implementation and the perceived effectiveness of collaboration, leading to the rejection of the null hypothesis. Policy and practice recommendations are proposed to enhance program sustainability.